Dynamics of Education of Fishermen's Children in Tanakeke Island in Phenomenological Perspective - Syarif, Erman (Indonesian Journal of Educational Studies, 2021)
This study aims: 1) how is the economic condition of parents in Balang Datu Village, Tanakeke District, Takalar Regency?, 2) What is the education level of fishermen's children in Balang Datu Village, Tanakeke District, Takalar Regency?. This type of research is qualitative research. This research was conducted in Balangdatu Village, Tanakeke District. Sources of data in this study are informants. Collecting data through observation, interviews, and documentation. Data verification strategy with data triangulation, member check, and audit trail. The results showed that 1) The economic conditions of parents in Balangdatu Village, Tanakeke District, Takalar Regency were mostly moderate, as many as 46%. 2) In general, fishermen's children who do not continue their education to the level of High School (SMA) and Higher Education (PT) because there are no costs or the economic conditions of their parents are less fortunate. This shows that the economic condition of parents is one of the factors that affect fishermen's children in Balangdatu Village, Tanakeke District, not continuing their education to the high school level.